2021
DOI: 10.3390/microorganisms9051094
|View full text |Cite
|
Sign up to set email alerts
|

Global Genomic Analysis of SARS-CoV-2 RNA Dependent RNA Polymerase Evolution and Antiviral Drug Resistance

Abstract: A variety of antiviral treatments for COVID-19 have been investigated, involving many repurposed drugs. Currently, the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp, encoded by nsp12-nsp7-nsp8) has been targeted by numerous inhibitors, e.g., remdesivir, the only provisionally approved treatment to-date, although the clinical impact of these interventions remains inconclusive. However, the potential emergence of antiviral resistance poses a threat to the efficacy of any successful therapies on a wide scale. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…The accessibility of real-world sequences from the expansive GISAID dataset has enabled a global, collaborative effort by scientists to track emerging lineages, identify signature escape mutations, and classify new variants in real time (18). To our knowledge, a comprehensive genomic surveillance of mutations in SARS-CoV-2 nonstructural proteins is limited to the RdRp (19, 20). Large-scale genetic surveillance of the M pro enzyme from circulating SARS-CoV-2 variants has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The accessibility of real-world sequences from the expansive GISAID dataset has enabled a global, collaborative effort by scientists to track emerging lineages, identify signature escape mutations, and classify new variants in real time (18). To our knowledge, a comprehensive genomic surveillance of mutations in SARS-CoV-2 nonstructural proteins is limited to the RdRp (19, 20). Large-scale genetic surveillance of the M pro enzyme from circulating SARS-CoV-2 variants has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Remdesivir resistance mutations have been characterized both clinically and experimentally. Unfortunately, one mutation conferring mild resistance does not carry any fitness cost in vitro [ 26 , 27 , 28 ]. If this mutant has no fitness costs in all relevant environments in the host and during transmission, we would expect it to arise quite frequently in remdesivir treated patients and ultimately to spread between patients, irrespective of mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, RDV inhibits the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp, encoded by nsp12-nsp7-nsp8), and mutations in RdRp can decrease sensitivity to RDV. Alarmingly, in vitro, these mutations leave viral fitness largely unaffected [ 26 , 27 , 28 ]. Thus, as we will show, resistance can easily be selected for by some RDV drug regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the scientists reported several mutations in RdRp variants [ 35 ]. However, Mari et al observed significant mutations in the RdRp (V557L, V473F, N491S, and F480L/S/C) that are significantly responsible for Remdesivir resistance [ 36 ]. It was noted that the V557L mutation in Nsp12 changes binding affinity to the RNA template and ultimately to remdesivir [ 37 ].…”
Section: Significant Mutations and Small Molecule-based Therapeutic Resistancementioning
confidence: 99%
“…Similarly, V473F is a potential escape mutation described by Mari et al It is one of the essential residues in the structural context of RdRp, which is associated with the fingers region. At the same time, researchers found an association between V473F mutation and an SNP, which is positioned at 24,378 genomic positions [ 38 ]. Simultaneously, scientists found that N491S in Nsp12 is associated with high-frequency nsSNPs (non-synonymous SNPs) related to escape mutations.…”
Section: Significant Mutations and Small Molecule-based Therapeutic Resistancementioning
confidence: 99%